Dilatation of the Great Arteries in an Infant with Marfan Syndrome and Ventricular Septal Defect. (12th July 2011) - Rozendaal, L.; Blom, N. A.; Hilhorst-Hofstee, Y.; Ten Harkel, A. D. J.
Abstract : We describe an infant presenting with contractures of the fingers, a large ventricular septal defect (VSD), and severe pulmonary artery dilatation. He had clinical and echocardiographic features of both neonatal or infantile Marfan syndrome (MFS) and congenital contractural arachnodactyly. After surgical VSD closure, the aortic root developed progressive dilatation while the size of pulmonary artery returned to normal limits. Eventually the diagnosis of MFS was confirmed by DNA analysis.